Comparison of point transect distance and traditional acoustic point‐count sampling of hoolock gibbons in Htamanthi Wildlife Sanctuary, Myanmar. Issue 12 (28th September 2020) - Brockelman, Warren Y.; Tun, Aung Ye; Pan, Su; Naing, Hla; Htun, Saw
Abstract: Effective conservation demands more accurate and reliable methods of survey and monitoring of populations. Surveys of gibbon populations have relied mostly on mapping of groups in "listening areas" using acoustical point‐count data. Traditional methods of estimating density in have usually used counts of gibbon groups within fixed‐radius areas or areas bounded by terrain barriers to sound transmission, and have not accounted for possible decline in detectability with distance. In this study we sampled the eastern hoolock gibbon ( Hoolock leucogenys ) population in Htamanthi Wildlife Sanctuary (WS), Myanmar, using two methods: the traditional point‐count method with fixed‐radius listening areas, and a newer method using point‐transect Distance analysis from a sample point established in the center of each listening point array. The basic data were obtained by triangulating on singing groups from four LPs for 4 days, in 10 randomly selected sample areas within the sanctuary. The point transect method gave an average density of 3.13 groups km −2, higher than the estimates of group density within fixed‐radius areas without correction for detectability. A new method of analysis of singing probability per day ( p [1]) gave an estimate of 0.547. Htamanthi WS is an important conservation area containing an estimated 7000 (95% confidence interval: 5000–10, 000) hoolock groups. Surveys at Htamanthi WS and locations in the Hukaung Valley suggest that the extensive evergreen forests in northern Myanmar have the capacity to support 2–4 (average about 3) groups of hoolock gibbons per km 2, but most forests in its range have yet to be surveyed. Abstract : In estimating the number gibbon groups by acoustic means, we must account for the fact that groups farther away have a lower probability of being heard. Shown here are two models for the probability of detection of gibbon groups at increasing distance from the sample point, fit to the actual data (histograms) on gibbon groups heard. Research Highlights: Surveys of gibbon populations employing better statistical methods yield higher population estimates than older, more "traditional, " methods. Htamanthi Wildlife Sanctuary in northern Myanmar is an important refuge for this Vulnerable ape species.